2020
DOI: 10.1155/2020/5023948
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis Intestinalis in Adult Bilateral Lung Transplant Patients: A Single Institution Experience and Literature Review

Abstract: Pneumatosis intestinalis (PI) is a radiologic finding which is characterized by the accumulation of gas within the bowel wall. This radiologic finding is traditionally thought of in the sense of intestinal ischemia. An uncommon cause of this finding is post organ transplantation. We did an institutional and literature review of this finding to demonstrate its distinct imaging features and benign nature. It was observed to occur in approximately 5.2% of patients post lung transplant (23/442). On imaging, it dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Less commonly, patients present, like case 2, with sudden acute‐on‐chronic worsening of severe nausea, nonbilious emesis, and retching. PI was identified in the cecum and ascending colon in both patients, a typical location for PI in the solid organ transplant population 1,7,9,10 …”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Less commonly, patients present, like case 2, with sudden acute‐on‐chronic worsening of severe nausea, nonbilious emesis, and retching. PI was identified in the cecum and ascending colon in both patients, a typical location for PI in the solid organ transplant population 1,7,9,10 …”
Section: Discussionmentioning
confidence: 92%
“…Possible contributing factors to the PI could have been the initial hypoperfusion related to the transplantation, the performance of endoscopy/colonoscopy, or the presence of a gastrojejunal tube immediately post‐transplantation 4 . One other study showed that placement of a gastrojejunostomy tube following transplant might be a risk factor for the development of PI 10 . Therefore, patients following lung transplantation may be at increased risk of endoscopy complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations